Silencing of VEGF inhibits human osteosarcoma angiogenesis and promotes cell apoptosis via VEGF/PI3K/AKT signaling pathway - Peng, Ningning (Am J Transl Res, 2016)
Background: Osteosarcoma is a kind of highly malignant tumor and the growth and metastasis is closely related to angiogenesis. Vascular endothelial growth factor (VEGF) is an important angiogenesis-promoting factor. In the current study, we investigated the effects of suppressed VEGF on osteosarcoma and its molecular mechanism provided for a basis by targeting angiogenesis. Material/Methods: We established bearing human osteosarcoma Wistar rats model by subcutaneous inoculation of human SaOS-2 cells and the adenovirus vector Ad-VEGF-siRNA was constructed for further study. We assessed the efficiency of VEGF silencing and its influence on SaOS-2 cells. The expression of mRNA and protein were detected by RT-PCR and western blotting, respectively. Intratumoral microvessel density (MVD), VEGF and CD31 were evaluated by immunohistochemistry. We detected the cell apoptotic rates by flow cytometry. Results: Our results indicated that Ad-VEGF-siRNA could effectively suppressed the expression of VEGF expression, inhibited the proliferation capability and promoted apoptosis of SaOS-2 cells in vitro. Silencing of VEGF expression also suppress osteosarcoma tumor growth and reduce osteosarcoma angiogenesis in the Wistar rats model in vivo. Furthermore, We found that phosphoinositide 3-kinase (PI3K) and protein kinase B (AKT) activation were considerably reduced while inhibition VEGF expression in SaOS-2 cells. Conclusion: Our data demonstrated that VEGF silencing could suppress cells proliferation, promote cells apoptosis and reduce osteosarcoma angiogenesis through inactivation of VEGF/PI3K/AKT signaling pathway.